THE INFLUENCE OF SOCIAL MEDIA MARKETING AND PRODUCT PLACEMENT OF COLORGRAM ON GENERATION Z PURCHASE INTENTION IN MANADO - Natasya Mamesah; S. L. H. V. J. Lapian; Regina T. Saerang (Universitas Sam Ratulangi, 2023)
Product Placement and Influencer Marketing are types of marketing strategy that uses media such as Movies and TV Shows and also social media. The product will be promoted throughout the show and also through famous influencer in order for the brand to gain more recognition. Brand awareness are customers’ ability to recall and to use the product from a certain brand after seeing them and to buy them in the future. This paper consists of study on Generation Z’s behavior especially for the awareness of the brand through product placement that appears on Movies and TV Shows and also Influencer Marketing across social media platform. The result was taken from 100 Generation Z who lives in Manado and have interest on Movies and TV Shows along with influencers on social media. According to the findings, the people found that product placement has a significant impact towards the awareness of the brand and that influencers marketing has less impact due to the lack of trust that they have on the review that was done by the influencers. Keyword: product placement, influencer marketing, brand awareness